2020
DOI: 10.1093/humrep/deaa184
|View full text |Cite
|
Sign up to set email alerts
|

A panel of extracellular vesicle long noncoding RNAs in seminal plasma for predicting testicular spermatozoa in nonobstructive azoospermia patients

Abstract: STUDY QUESTION Whether the testis-specific extracellular vesicle (EV) long noncoding RNAs (lncRNAs) in seminal plasma could be utilized to predict the presence of testicular spermatozoa in nonobstructive azoospermia (NOA) patients? SUMMARY ANSWER Our findings indicate that the panel based on seminal plasma EV lncRNAs was a sensitive and specific method in predicting the presence of testicular spermatozoa and may improve clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 30 publications
1
39
0
Order By: Relevance
“…1D ). It was recently reported that LINC01921 is significantly decreased or differentially expressed in patients with nonobstructive azoospermia ( 49 ). Although further investigation is required to determine whether a decrease in the expression levels of LINC01921 is directly involved in nonobstructive azoospermia, this human lncRNA Teshl ortholog could be considered a suitable biomarker for diagnosis of human infertility.…”
Section: Discussionmentioning
confidence: 99%
“…1D ). It was recently reported that LINC01921 is significantly decreased or differentially expressed in patients with nonobstructive azoospermia ( 49 ). Although further investigation is required to determine whether a decrease in the expression levels of LINC01921 is directly involved in nonobstructive azoospermia, this human lncRNA Teshl ortholog could be considered a suitable biomarker for diagnosis of human infertility.…”
Section: Discussionmentioning
confidence: 99%
“…Çayan et al reported a study that NOA men with a history of cryptorchidism have high sperm retrieval rates with mTESE [ 9 ]. However, some studies have shown that there are no precise and noninvasive methods for predicting whether there are testicular spermatozoa in NOA patients before mTESE [ 10 ]. Maglia et al found that the success rate of sperm retrieval in NOA patients was similar between the mTESE group and the conventional TESA group, and mTESE seemed to be more beneficial for patients over 35 years of age and with high FSH value [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the predictive value of these biomarkers has predominantly been observed in only one study with a small number of NOA men and consequently is inconclusive and questionable. In support of this, while miR-539-5p emerged as a good predictor of successful sperm recovery in one study [50], it exhibited no predictive value regarding TESE outcome in another study [51]. Hence, it seems reasonable to assume that further examining the predictive potential of the aforementioned molecular biomarkers can provoke similar controversy observed for hormonal markers.…”
Section: Conclusion and Prospectmentioning
confidence: 93%
“…Likewise, a seminal panel of exosomal long non-coding RNAs (lncRNAs) elicited from NOA patients displayed an outstanding predictive value in terms of sperm retrieval rate according to a recent report. Interestingly, the aforementioned lncRNA panel had remarkably higher predictive precision for the recovery of sperm from the testicular biopsies of NOA men in comparison with two different hormone-based models [51]. Moreover, there are numerous studies that evaluated seminal plasma proteome in azoospermic patients, although the majority of them have focused on the diagnosis and differentiation of azoospermia subclasses, i.e., OA and NOA, rather than the success of TESE outcome.…”
Section: Conclusion and Prospectmentioning
confidence: 99%